Climate Change Adaptation. Challenges and Opportunities for a Smart Urban Growth - Galderisi, Adriana (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Climate change is one of the main environmental issues challenging cities in the 21th century. At present, more than half of the world population lives in cities and the latter are responsible for 60% to 80% of global energy consumption and greenhouse gas (GHG) emissions, which are the main causes of the change in climate conditions. In the meantime, they are seriously threatened by the heterogeneous climate-related phenomena, very often exacerbated by the features of the cities themselves. In the last decade, international and European efforts have been mainly focused on mitigation rather than on adaptation strategies. Europe is one of the world leaders in global mitigation policies, while the issue of adaptation has gained growing importance in the last years. As underlined by the EU Strategy on adaptation to climate change, even though climate change mitigation still remains a priority for the global community, large room has to be devoted to adaptation measures, in order to effectively face the unavoidable impacts and related economic, environmental and social costs of climate change (EC, 2013). Thus, measures for adaptation to climate change are receiving an increasing financial support and a growing number of European countries are implementing national and urban adaptation strategies to deal with the actual and potential climate change impacts. According to the above considerations, this paper explores strengths and weaknesses of current adaptation strategies in European cities. First the main suggestions of the European Community to improve urban adaptation to climate change are examined; then, some recent Adaptation Plans are analyzed, in order to highlight challenges and opportunities arising from the adaptation processes at urban level and to explore the potential of Adaptation Plans to promote a smart growth in the European cities.